Acute lymphoblastic leukaemia cells produce large extracellular vesicles containing organelles and an active cytoskeleton. Issue 1 (1st December 2017) - Johnson, Suzanne M.; Dempsey, Clare; Parker, Catriona; Mironov, Aleksandr; Bradley, Helen; Saha, Vaskar
ABSTRACT: Extracellular vesicles have been described in non‐paracrine cellular interactions in cancer. We report a similar phenomenon in B‐cell precursor (BCP) acute lymphoblastic leukaemia (ALL). Using advanced microscopy and high throughput screening, we further characterise a subset of large vesicles (LEVs) identified in cell lines, murine models of human BCP‐ALL and clinical samples. Primary ALL blasts and cell lines released heterogeneous anucleate vesicles <6 micron into extracellular fluids. Larger LEVs were enclosed in continuous membranes, contained intact organelles and demonstrated an organised cytoskeleton. An excess of circulating CD19‐positive LEVs were observed in diagnostic samples and isolated from mice engrafted with BCP‐ALL primary cells. LEVs exhibited dynamic shape change in vitro and were internalised by other leukaemic cell lines leading to phenotypic transformation analogous to the cell of origin. In patient‐derived xenografts, LEVs were released by primary ALL cells into extracellular spaces and internalised by murine mesenchymal cells in vivo . Collectively these data highlight the heterogeneity but accessibility of LEVs in clinical samples and their potential to provide a unique insight into the biology of the cell of origin and to their development as novel biomarkers to aid diagnosis and improve therapeutic outcomes.